What Workers Say: Employee Voice in the Anglo-American Workplace - Spencer, Bruce (Labour / Le Travail, 2008)
The article reviews the book, "What Workers Say: Employee Voice in the Anglo-American Workplace," edited by Richard B. Freeman, Peter Boxall and Peter Haynes.
Keywords: BOOKS -- Reviews; BOXALL, Peter; Employees; FREEMAN, Richard B.; HAYNES, Peter; Nonfiction; WHAT Workers Say: Employee Voice in the Anglo-American Workplace (Book)